Faktor-Faktor Sosisologis Yang Terlihat Dalam Perintisan Jemaat - Anessa Mei Pasaribu; Sisga Desriman Zebua; Reni Herayani Manik; Megawati Manullang (Universitas Katolik Widya Karya Malang, 2023)
Church planting is not a new thing in the journey of Christianity and has an important role to play in the continuation of God's work on earth. Church planting is one aspect that plays an important role in the growth of the church as well as something that the church must do, not only the church, but all believers, considering this duty and responsibility is contained in the Great Commission. David Garrison suggests 4 classifications of church planting, namely rapidly multiplying, indigenous, church planting and in tribal groups. The segmentation of church planting is aimed at both unbelievers and believers who are immature in faith and unshepherded. In new church planting, the above are important factors that will help new churches grow and develop well. However, the sociological factors seen in new church planting vary depending on the case being analyzed, but God does not ignore the physical needs of people. When Jesus ministered in the world, He performed many social acts, such as healing diseases and feeding people. Evangelism is not one of our efforts to separate them from their culture, we still live culturally and maintain that culture, but our job is to straighten their path from the wrong to the right path, namely the Lord Jesus Christ who is the Savior of mankind. We must keep and preserve the culture, but it is the wrong way and understanding that we must correct.